Ecological and Morphological Profile of Floating Spherical Cladophora socialis Aggregations in Central Thailand - Isao Tsutsui; Tatsuo Miyoshi; Halethichanok Sukchai; Piyarat Pinphoo; Dusit Aue-Umneoy; Chonlada Meeanan; Jaruwan Songphatkaew; Sirimas Klomkling; Iori Yamaguchi; Monthon Ganmanee; Hiroyuki Sudo; Kaoru Hamano (My University, 2015)
The unique beauty of spherical aggregation forming algae has attracted much attention from both the scientific and lay communities. Several aegagropilous seaweeds have been identified to date, including the plants of genus Cladophora and Chaetomorpha. However, this phenomenon remains poorly understood. In July 2013, a mass occurrence of spherical Cladophora aggregations was observed in a salt field reservoir in Central Thailand. The aims of the present study were to describe the habitat of the spherical aggregations and confirm the species. We performed a field survey, internal and external morphological observations, pyrenoid ultrastructure observations, and molecular sequence analysis. Floating spherical Cladophora aggregations (1–8 cm in diameter) were observed in an area ~560 m2, on the downwind side of the reservoir where there was water movement. Individual filaments in the aggregations were entangled in each other; consequently, branches growing in different directions were observed within a clump. We suggest that water movement and morphological characteristics promote the formation of spherical aggregations in this species. The molecular sequencing results revealed that the study species was highly homologous to both C. socialis and C. coelothrix. However, the diameter of the apical cells in the study species was less than that of C. coelothrix. The pyrenoid ultrastructure was more consistent with that of C. socialis. We conclude that the study species is C. socialis. This first record of spherical aggregations in this species advances our understanding of these formations. However, further detailed physical measurements are required to fully elucidate the mechanism behind these spherical formations.
Keywords: Pyrenoid; Cladophora; Marine and coastal plant biology